2014
DOI: 10.1016/j.jtcvs.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Denervation of gastroepiploic artery graft can reduce vasospasm

Abstract: The removal of the periarterial sympathetic nerve from the human gastroepiploic artery reduced vascular contraction, elicited by peripheral nerve stimulation, without disturbing endothelial and smooth muscle contractile functions. This reduction may contribute to the prevention of vasospasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Likewise, it has also been reported that denervation or skeletonization of the graft may reduce vasospasm of the GEA [8,77] and RA [78]. However, the impact of denervation or skeletonization on the graft spasm or patency has yet to be definitively confirmed.…”
Section: Principles Of Prevention Of Spasm In Arterial Graftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it has also been reported that denervation or skeletonization of the graft may reduce vasospasm of the GEA [8,77] and RA [78]. However, the impact of denervation or skeletonization on the graft spasm or patency has yet to be definitively confirmed.…”
Section: Principles Of Prevention Of Spasm In Arterial Graftsmentioning
confidence: 99%
“…Consider denervation or skeletonization. It has been hypothesized that denervation or skeletonization of the arteries used for grafting may disrupt the periarterial sympathetic nerves and prevent spasm [8].…”
Section: Principles Of Prevention Of Spasm In Arterial Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletonization of grafts was initially used in IMA. It has been suggested that skeletonized arterial graft may denervate the vessel, reduce the risk of spasm, and improve graft patency in GEA [67][68][69] and RA [35], and this is often done with the ultrasonic scalpel [69]. Conversely, studies have demonstrated that skeletonization with an ultrasonic scalpel did not result in additional length and was more frequently associated with severe endothelial damage [70], and that en bloc free GEA graft, which has the gastroepiploic vein anastomosed to the right atrial appendage [71], can prevent graft spasm, leading to improved patency rate.…”
Section: Skeletonization Denervation or En Bloc Harvesting?mentioning
confidence: 99%
“…78) While offering superior long-term outcomes to SVGs, 18) there is considerable individual variability in characteristics, and arteriosclerosis is sometimes a problem. Although denervation by performing a skeletonized harvest has been experimentally shown to suppress spasms 24,79) tonus is also increased when compared with ITA grafts. 80) When using the GEA for in situ grafts, the anatomic target is the right coronary artery or the distal the circumflex branch.…”
Section: Gastroepiploic Arterymentioning
confidence: 99%